ANALISIS PERENCANAAN KEBUTUHAN SUMBER DAYA MANUSIA KEPOLISIAN PADA SATUAN POLRES FAKFAK - Sulistiyono, Sulistiyono; Murary, Weron; Baho, Dayen (Ensiklopedia of Journal, 2025)
Human resources play an important role in their success in achieving the goals that have been set, the success of the National Police as a public organization that prioritizes service to the community in achieving its goals is highly dependent on the availability and quality of its human resources. The National Police is an auxiliary element of the Leadership who is in charge of managing human resources so that it is able to provide quality and sufficient human resources for the National Police. Regarding the development of human resources of the National Police, in Article 21 paragraph 2 of Law Number 2 of 2002, it is stated that the development of members of the National Police of the Republic of Indonesia includes the provision, education, use, maintenance and termination of service. Competent and professional human resources are very important at the Fakfak Police, because they are the spearhead in maintaining order and security in the area.Research in this problem uses normative juridical research, to find legal rules, legal principles, and legal doctrines to answer the legal issues faced. Primary data, is an authoritative legal material which means it has authority or can be interpreted as legal material used as the main source in this study, then the author conducts this research using structured interviews, which are arranged in detail so that nothing is missed when interviewing respondents, data analysis to process data into information so that the characteristics of the data can be understood and useful for problem solving, especially problems related to research.From the results of the research, it was found that the need for human resources at the Fakfak Police is needed a comprehensive and effective strategy, important steps in recruitment and quality selection include planning for labor needs, promotion of attractive job vacancies, strict selection process, competency tests, integrity and morality assessments, training and orientation, and monitoring and evaluation of the performance of new employees, with the implementation of this strategy,  The Fakfak Police can ensure that they get human resources who are competent, have integrity, and are ready to carry out their duties well. Shortages of personnel lead to increased workloads, slow responses, less effective oversight, and limitations in law enforcement. Limited infrastructure, budget, and technical equipment affect day-to-day operations and effectiveness in law enforcement. Changing values and norms, urbanization, technology, and generational differences demand adjustments in police approaches and policies. The appointment and promotion process must be based on qualifications, performance, training, and periodic evaluations, and be conducted fairly and transparently. Keywords: Needs, Human Resources, Police, Fakfak Police